Case Report: Totally endoscopic minimally invasive mitral valve surgery during pregnancy: a case series - Wang, Zhenzhong; Zhong, Lishan; Guo, Haijiang; Liu, Yanli; Zhou, Chengbin; Ye, Yingxian; Han, Fengzhen; Huang, Huanlei (Frontiers in Cardiovascular Medicine, 2024)
A totally endoscopic minimally invasive approach is widely used for cardiac valve surgery in normal adults. However, minimally invasive cardiac surgery during pregnancy is rarely reported. In addition to traditional median thoracotomy, totally endoscopic minimally invasive approaches can now be used for pregnant patients. We describe our experience with totally endoscopic cardiac valve surgery (TECVS) during pregnancy, which is safe for both mothers and fetuses.